Patient safety culture in resource-limited healthcare settings: A multicentre survey - Gelana Fekadu; Rachel Muir; Georgia Tobiano; Aman Edao Bime; Michael J. Ireland; Andrea P. Marshall (PLoS ONE, 2025)
Objective: To assess healthcare professionals’ perceptions of patient safety culture and to examine variations across clinical units in Eastern Ethiopian public hospitals. Methods: A cross-sectional study was conducted using the Hospital Survey on Patient Safety Culture (HSoPSC 2.0) tool. Analysis of variance and ordinal logistic regression analyses were performed. Results were presented as mean differences and an adjusted odds ratio (AOR) with a 95% confidence interval (CI), and statistical significance was set at a p-value < 0.05. Content analysis was performed for data provided through the open-ended response option. Results: A total of 582 questionnaires were returned, yielding a response rate of 85%. Overall positive patient safety culture score was 47% (95% CI: 41–53%). Intensive care units (ICUs) scored significantly lower on patient safety culture dimensions compared to other clinical units. Factors contributing to the patient safety ratings included Midwives (AOR = 0.20, 95% CI: 0.06–0.71, p = 0.013), Organisational learning and continuous improvement (AOR = 1.35, 95% CI: 1.04–1.76, p = 0.025), Supervisor, manager, or clinical leader support for patient safety (AOR = 1.41, 95% CI: 1.06–1.89, p = 0.02), and Hospital management support for patient safety (AOR = 1.28, 95% CI: 1.00–1.63, p = 0.049). The challenges in ensuring patient safety included the absence of patient safety incident reporting systems, severe resource constraints, limited awareness regarding patient safety, ineffective communication, poor management support, and a blame-oriented organisational culture. Conclusions: Significant improvement in patient safety culture in Ethiopian public hospitals, especially in the ICU, is critically needed to mitigate healthcare risks and ensure patient safety. Addressing these issues requires targeted patient safety training, strong leadership support, and adequate resource allocation. Further exploration of ICU-specific patient safety insights and validation of the HSoPSC 2.0 tool within the Ethiopian healthcare context should be undertaken to ensure cultural and contextual relevance.